Por uma justiça de transição efetiva: análises crítico-jurídicas da atuação do Ministério Público Federal na promoção das ações judiciais destinadas à implementação das dimensões fundamentais da justiça transicional - André de Oliveira Morais (2013)
The Brazil experienced between 1964 and 1985, a civil-military dictatorship. During the period, democracy was weakened and numerous human rights violations perpetrated by the state. Paradoxically, even after more than 25 years of democracy, the country has not effected the implementation of the postulates of Transitional Justice, steps in which society is called to examine the history and outline the basis on which claims to base their political and social life. The few measurements are structured only around the axis reparations. In this sense, this thesis focuses on initiatives in civil and criminal motions by federal prosecutors with a view to ensuring the right of recourse in the face of state agents that motivated, because of their wicked acts, the payment of various claims, by the State, victims of the military regime and their families, causing losses to the public, and the prosecution of these agents, in order to calculate the individual responsibilities, in order to mitigate a history of impunity that still persists. To do so, it begins plotting an overview of the concept "Transitional Justice" and its current stage of implementation in the Brazilian perspective. Then go to the analysis of specific cases, which were demanded before the federal court. Concomitantly, do it are some reflections on the activities of members of federal and parquet tract of federal judges with issues relating to transitional justice, concluding that Brazil has not effected the process of reckoning with its repressive past, as there was little concrete institutional response to the crimes of the dictatorship, there are internal contradictions to be resolved by the federal ministerial institution, in order to strengthen the principle of unity, and, finally, it appears that federal judges are not familiar with the postulates of International Law, so little with the opening dialogue of constitutional sources.